2013
DOI: 10.1007/s12272-013-0115-5
|View full text |Cite
|
Sign up to set email alerts
|

Clauraila E from the roots of Clausena harmandiana and antifungal activity against Pythium insidiosum

Abstract: A new carbazole alkaloid named clauraila E (1) together with 8 known compounds were isolated from the methanol extract of the roots of Clausena harmandiana. All compounds were evaluated for antifungal activity against Pythium insidiosum using disc diffusion assay. Pythium insidiosum is a fungus-like microorganism, for which antifungals available now are not effective. It was found that compounds 3, 6, 7 and 9 could inhibit the mycelia growth of P. insidiosum. The results show convincingly that they may be lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Prior studies demonstrated the susceptibility of P. insidiosum to antifungal agents [4,9,10,30], antibiotics [20,21,23] 1 and compounds derived from plants and fungi [16,[34][35][36] in vitro. However, tests of drug combinations were performed mainly with antifungal agents, which showed synergistic interactions of 11.8% to 46.7%, particularly when TRB was combined with other antifungal drugs [3,4,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies demonstrated the susceptibility of P. insidiosum to antifungal agents [4,9,10,30], antibiotics [20,21,23] 1 and compounds derived from plants and fungi [16,[34][35][36] in vitro. However, tests of drug combinations were performed mainly with antifungal agents, which showed synergistic interactions of 11.8% to 46.7%, particularly when TRB was combined with other antifungal drugs [3,4,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…In continuation of our research on bioactive compounds from medicinal plants [5], we have intensively screened the natural compounds against Pythium insidiosum [6]. P. insidiosum is not a true fungus because its cell walls do not contain ergosterol which is the target for antifungal agents and in addition, it is closely related to diatoms and golden-brown algae [7].…”
Section: Introductionmentioning
confidence: 99%
“… 24 In Thailand, the disease is endemic for humans and the effects of traditional medicinal plants ( Alyxia schlechteri and Clausena harmandiana roots) were investigated, showing that some compounds were able to inhibit the mycelia growth of the pathogen. 25 , 26 …”
Section: Discussionmentioning
confidence: 99%